Socio-educational home environment in relation to students mathematics achievements - Dudaitė, Jolita (Lietuvos matematikos rinkinys, 2005)
The article deals with impact of socio-educational home environment on Lithuanian Grade 8 students' mathematics achievements. Data of the Trends in International Mathematics and Science Study (TIMSS) is used for analysis. The results show high correlation between Lithuanian Grade 8 students' mathematics achievements and home-related factors. The higher relation is seen between mathematics achievements and educational home environment than between mathematics achievements and economical home environment.
Keywords: mathematics achievements; socio-educational environment